Representações e orientações do movimento sindical face ao trabalho e ativismo feminino em Portugal, 1850-1926 - Joana Dias Pereira (Ler História)
The relationship between class and gender has been the subject of numerous international studies. In Portugal, however, this is an under-researched topic. This article focuses on the emergence of a new repertoire of women's collective actions during Portuguese industrialisation and the resulting trade union representations on and orientations for working women. It is based on the study of the workers’ press and the theses adopted at the trade union congresses between 1890 and 1926. This article shows that working women simultaneously challenged the social role imposed on them and the over-exploitation. This led to contradictory representations and orientations within the labour movement, resulting in resistance to women’s associative participation coexist with manifestations of solidarity and articulation between male and female struggles. Deepening this analysis is fundamental to overcoming simplifications and understanding the role of women and the feminisation of labour in the emergence of the labour movement in Portugal.